The Mindful Way Through the Semester: An Investigation of the Effectiveness of an Acceptance-Based Behavioral Therapy Program on Psychological Wellness in First-Year Students. (July 2014) - Danitz, Sara B.; Orsillo, Susan M.
First-year students in higher education deal with an increasing number of mental health issues. Cost-effective and time-efficient programs that ease transitions and reduce risk of depression are needed. To date, programs informed by both cognitive-behavioral and acceptance-based-behavioral therapy (ABBT) approaches have produced some positive outcomes, but methodological limitations limit their utility. The aim of the present study was to address some of these limitations, by developing and preliminary testing the efficacy of a one-session ABBT intervention with first-year undergraduates and first-year law students. Ninety-eight first-year students were randomly assigned to receive either a single-session 90-min ABBT workshop within their first month of school or to a waitlist control condition. Students who received the intervention reported significantly less depression and more acceptance. Moreover, increase in acceptance over the course of the semester was associated with reductions in depression. Implications of these findings for future interventions are discussed.